Penerapan Blending Kitosan-Tonasi Terhadap Pertumbuhan Dan Produktivitas Buah Kakao (Theobroma cacao L.) (Studi Wilayah Kabupaten Sigi) - Nur Asmara; Suherman Suherman; Siang Tandi Gonggo (Universitas Tadulako, 2015)
The cocoa (theobroma cacao L.) plant is one of the plantation crops which has an economic potential value. Chitosan and cacao tonnage are potential to be used as nutrients in cacao plant. This research was aimed to use blending chitosan and tonnage dust of cocoa as a suplement in cocoa plant. Method of the research used comparisons of the amount of capsule blending chitosan and tonnage for fertilizing. Comparisons of the blending chitosan tonnage used as the test groups were 16 capsules, 12 capsules, and 8 capsules added by pesticide. As a positive control was the commercial fertilizer with additional of pesticide, and the negative control used only pesticide. Physical observations before and after treatments showed that the test groups and the positive control were able to reduce the amount of tonnage, and improved quality of the skin and the cocoa beans. Each group of 16 capsules, 12 capsules, 8 capsules, positive control and negative control produced weight for every three cocoa beans of 129.25 g, 128.88 g, 96.87 g, 115.22 g, and 44.76 g, respectively. While the cocoa fat level analysis of each sample showed 54.53%, 52.60%, 52.02%, 51.87%, and 48.39%, respectively. It can be concluded that the blending chitosan tonnage increased the productivity and the quality of cocoa beans.